2023
DOI: 10.18502/ssu.v30i11.11783
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Psychiatric Disorders and the Relevant Comorbidities in Children and Adolescents in Yazd Province in 2016

Abstract: Introduction: Due to significant social, economic, cultural, and lifestyle changes in Iran during past decades and the relationship among the unstable social and economic status and mental complications the study of psychiatric disorders has become important and necessary, the aim of this study was epidemiology of psychiatric disorders in children and adolescents. Methods: A total of 1035 children aged 6-18 years from Yazd Province, Iran were enrolled in this cross-sectional study in 2017 using a multist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…A research study conducted in Kurdistan reported a 1 percent prevalence rate for autism disorder. (51) Sampling and participants…”
Section: Contextmentioning
confidence: 99%
“…A research study conducted in Kurdistan reported a 1 percent prevalence rate for autism disorder. (51) Sampling and participants…”
Section: Contextmentioning
confidence: 99%
“…Based on studies, adolescent girls' challenges in health can be classified into social and cultural challenges such as taboos and structural and administrative challenges when seeking health care (Mirzaii Najmabadi et al, 2018). Exact statistics of the prevalence of psychiatric disorders are not available in Iran (Mohammadzadeh et al, 2018). According to reports, roughly 17.9% of children aged between 6 and 11 years suffer from psychiatric disorders (Mohammadi et al, 2019).…”
mentioning
confidence: 99%